A Few Transformations and Comments Concerning a Programme, Used in Management of Time for Different Projects - RĂDESCU, Octavian Dan (Journal of Advanced Research in Management; Vol 8 No 1 (2017): JARM Volume VIII Issue 1(15) Summer 2017, 2017)
In the study of time management it is settled a graph of a work programme and starting from the order relations existent between different operations, then, the way of the critical path enabled the lets say approximate deduction of the realization date of the works ‘ensemble, fluctuation intervals, etc. Actually the way of the critical path is not by itself a method of order if is applied only for the already settled graph programme, meaning in the moment when the order of things has been done. Its role actually is to interpretate the graph from a temporal point of view and gives all the indications needed concerning the realization dates of different events of the programme or to enable the testing of different graphs of the same ensemble of works. Next, using a decomposition of a graph, notion that belongs to us and for which we give the determinating algorithm, we will put in a linear way all the connection between the activities included in the programme, which after a good partial analysis on pieces and then the global analysis of the programme given, using the corresponding programme graph.